1996
DOI: 10.1002/(sici)1096-9861(19960610)369:4<483::aid-cne1>3.0.co;2-0
|View full text |Cite
|
Sign up to set email alerts
|

Selective distribution of the NMDA-R1 glutamate receptor in astrocytes and presynaptic axon terminals in the nucleus locus coeruleus of the rat brain: An immunoelectron microscopic study

Abstract: The regional and cellular distribution of the different classes of excitatory amino acid receptors with respect to the noradrenergic neurons of the nucleus locus coeruleus (LC) are unknown. We therefore combined immunoperoxidase labeling for the R1 subunit of the N-methy-D-aspartate (NMDA) receptor with immunogold-silver localization of the catecholamine synthesizing enzyme, tyrosine hydroxylase (TH), in single sections through the rat LC to determine the subcellular localization of this glutamate receptor sub… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
28
0

Year Published

1997
1997
2013
2013

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 48 publications
(35 citation statements)
references
References 63 publications
6
28
0
Order By: Relevance
“…These data suggest that NMDA receptors play a role in the regulation of GABAergic transmission. Overall, these data are consistent with previous demonstrations that presynaptic NMDA receptors contribute to NMDA-mediated phenomena in other regions of the nervous system (58)(59)(60)(61)(62)(63)(64).…”
supporting
confidence: 93%
“…These data suggest that NMDA receptors play a role in the regulation of GABAergic transmission. Overall, these data are consistent with previous demonstrations that presynaptic NMDA receptors contribute to NMDA-mediated phenomena in other regions of the nervous system (58)(59)(60)(61)(62)(63)(64).…”
supporting
confidence: 93%
“…Finally, it remains unclear whether the neuronal-to-glial communication mediated by NMDA receptors occur only in cortex, or they may also be present in other brain regions. The NMDA receptor proteins were predominantly identified in cortical astrocytes (Conti et al, 1997 but not in hippocampus (Krebs et al, 2003); there are some indications for NMDA receptors expression in astroglial cells in nucleus locus ceruleus (Van Bockstaele and Colago, 1996). Interestingly, reactive gliosis induced by ischemia led to an appearance of NMDA receptor subunits in hippocampal astrocytes (Gottlieb and Matute, 1997;Krebs et al, 2003).…”
Section: Nmdars Are Involved In Neuronal-glial Communicationsmentioning
confidence: 98%
“…Subunits of NMDA receptors (NR1 and NR2A/B) and expression of NMDA receptor mRNA were detected in astrocytes by immunohistochemistry, in situ hybridization, and PCR (Conti et al, 1996(Conti et al, , 1997Van Bockstaele and Colago, 1996;Schipke et al, 2001). Several functional studies demonstrated NMDAmediated currents and NMDA-induced [Ca 2ϩ ] i responses in cultured astrocytes (Kondoh et al, 2001) and in astrocytes in situ (Muller et al, 1993;Shao and McCarthy, 1997;Ziak et al, 1998;Schipke et al, 2001).…”
Section: Introductionmentioning
confidence: 99%
“…Stimulation of NMDARs results in, at least in part, the activation of nNOS. The LC region contains NMDAR (Allgaier et al, 2001;Shaw et al, 1992;Van Bockstaele and Colago, 1996), neuronal nitric oxide synthase (nNOS)-positive neurons (Cuellar et al, 2000;Karolewicz et al, 2004;Xu et al, 1994), and guanosine 3 0 ,5 0 cyclic monophosphate (cGMP) (Vulliemoz et al, 1999;Xu et al, 1998), suggesting the existence of a glutamate/nitrergic transduction pathway. The exact cellular localization of these glutamate/nitrergic signaling proteins within the human LC is still unknown.…”
Section: Introductionmentioning
confidence: 99%